2013
DOI: 10.1055/s-0033-1347912
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Esophageal Anastomosis

Abstract: After repair of esophageal atresia (EA) in a newborn, esophageal dysmotility presenting as dysphagia and symptomatic gastroesophageal reflux are common. Significant esophageal morbidity associated with EA extends into adulthood. In adulthood approximately one-fifth of the patients have developed epithelial metaplastic changes, one-third of these have intestinal metaplasia (Barrett esophagus). Surgical complications, increasing age, and impaired esophageal motility predict the development of epithelial metaplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…Dysphagia is a common problem [12, 20, 23]. Due to the dysphagia, many children develop adaptive feeding behaviours [11, 20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysphagia is a common problem [12, 20, 23]. Due to the dysphagia, many children develop adaptive feeding behaviours [11, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dysphagia, many children develop adaptive feeding behaviours [11, 20]. Dysphagia can occur in association with gastro-oesophageal reflux [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective series reported an increased incidence of ASs in children with GERD (3, 4). AS is reported as a possible complication also in the 8–15% of adult AE patients; as these strictures most likely arise as a result of prolonged acidic reflux, the far-reaching significance of GERD in these adult patients is further underlined (37). However, a multivariate analysis showed the absence of an association between GERD and subsequent stricture formation, probably due to the prescription of a systematic proton pump inhibitor (PPI) (7).…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…Follow-up studies have shown that most EA patients have a favourable long-term outcome despite persistant digestive and respiratory problems. Common gastrointestinal symptoms after EA repair are dysphagia and gastroesophageal reflux (GER) in up to 72% and 67% of the patients, respectively[ 4 , 5 ]. Chronic GER after EA repair might lead to mucosal damage, esophageal stricturing, Barrett’s esophagus and eventually esophageal adenocarcinoma (EAC)[ 5 - 8 ].…”
Section: Introductionmentioning
confidence: 99%